Nutritional and Food Composition Survey of Major Pulses Toward Healthy, Sustainable, and Biofortified Diets - Langyan, Sapna; Yadava, Pranjal; Khan, Fatima Nazish; Bhardwaj, Ragini; Tripathi, Kuldeep; Bhardwaj, Vikash; Bhardwaj, Rakesh; Gautam, Raj Kumar; Kumar, Ashok (Frontiers in Sustainable Food Systems, 2022)
The world's food demand is increasing rapidly due to fast population growth that has posed a challenge to meeting the requirements of nutritionally balanced diets. Pulses could play a major role in the human diet to combat these challenges and provide nutritional and physiological benefits. Pulses such as chickpeas, green gram, peas, horse gram, beans, lentils, black gram, etc., are rich sources of protein (190–260 g kg−1), carbohydrates (600–630 g kg−1), dietary fibers, and bioactive compounds. There are many health benefits of phytochemicals present in pulses, like flavonoids, phenolics, tannins, phytates, saponins, lectins, oxalates, phytosterols peptides, and enzyme inhibitors. Some of them have anti-inflammatory, anti-ulcerative, anti-microbial, and anti-cancer effects. Along with these, pulses are also rich in vitamins and minerals. In this review, we highlight the potential role of pulses in global food systems and diets, their nutritional value, health benefits, and prospects for biofortification of major pulses. The food composition databases with respect to pulses, effect of processing techniques, and approaches for improvement of nutritional profile of pulses are elaborated.